Integrating Artificial Intelligence (AI) into EFL in Higher Education: Challenges and Opportunities for Indonesian Teachers and Students - Sitti Maryam Hamid; Andi Bulkis Maghfirah Mannong; Saiful Saiful; Nico Irawan (STAI Hubbulwathan Duri, 2025)
Artificial intelligence (AI) is increasingly embedded in English as a Foreign Language (EFL) learning, offering both pedagogical opportunities and challenges in higher education. Understanding how teachers and students employ AI platforms is essential to optimize their benefits while addressing potential risks. This study employed a mixed-methods approach at a private university in Makassar. Quantitative data were collected through surveys involving 70 students and 35 English teachers, while qualitative insights were obtained from in-depth interviews with 30 students and 15 teachers. Data triangulation ensured reliability across survey and interview findings. Survey results showed differences in AI platform usage between teachers and students. Teachers primarily used QuillBot for paraphrasing, Turnitin for plagiarism detection, ChatGPT for chatbots, and Hello English for English-based learning. Students favored HIX.AI for paraphrasing, GPTZero for plagiarism, DeepSeek for chatbot interaction, and ELSA for English practice. Both groups frequently used DeepL as a translation tool. Interview data revealed challenges for teachers, including balancing facilitator roles with AI use, limited platform updates, accessibility barriers, and high costs of premium versions. Students’ challenges included overreliance on AI and limited access due to paid subscriptions. The findings highlight both opportunities and constraints in AI-assisted EFL learning. While AI enhances personalization and efficiency, it risks dependency and inequity in access. The study underscores the need for digital literacy training for teachers, institutional support for equitable access, and the development of adaptive AI-based learning models tailored to local contexts.